2009
DOI: 10.2174/157016209789973682
|View full text |Cite
|
Sign up to set email alerts
|

Increased CCL2 Expression and Macrophage/Monocyte Migration During Microbicide-Induced Vaginal Irritation

Abstract: Despite availability of successful prevention strategies, HIV continues to spread at alarming rates, especially among women in developing countries. Vaginal microbicides offer a promising approach for blocking transmission of HIV when condom use cannot be negotiated with male partners. A major problem in the development of vaginal microbicides is chemically induced vaginal irritation, which can enhance the risk of HIV transmission. Evaluation of vaginal irritation prior to clinical trials typically uses an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…5 C ), IL-1β, and TNF-α (data not shown). These cytokines and chemokines were selected because they have been shown to be up-regulated by other candidate microbicides and because they may play a role in microbicide-mediated enhancement of HIV-1 infection (1618). BTA-EG 6 did not lead to the release of any of these cytokines or chemokines, even at the highest doses tested.…”
Section: Resultsmentioning
confidence: 99%
“…5 C ), IL-1β, and TNF-α (data not shown). These cytokines and chemokines were selected because they have been shown to be up-regulated by other candidate microbicides and because they may play a role in microbicide-mediated enhancement of HIV-1 infection (1618). BTA-EG 6 did not lead to the release of any of these cytokines or chemokines, even at the highest doses tested.…”
Section: Resultsmentioning
confidence: 99%
“…Although, we similarly observed that a low concentration of BAK (33 nM or 10 −5 %) did not induce CCL4 production by THP-1 cells, this concentration of BAK could induce cytokines production by macrophages (THP-1 differentiated cells). It has been previously shown that BAK induced the release of inflammatory cytokines (IL-1β, CXCL1, CCL3, CCL5) and IL-1β, CXCL8/IL-8 and CCL2/MCP-1 by vaginal parenchyma [34], [35]. On ear tissues, application of BAK has been shown to release inflammatory cytokines such as TNF-α, IL-1β and MIP-1α and MIP-1β [36].…”
Section: Discussionmentioning
confidence: 99%
“…While N9, BZK, and SDS were selected as positive controls in models of vaginal irritation and inflammation, as reported in previous works (2,9,13,15,16), carboxymethyl cellulose (CMC; which is widely used as a microbicide excipient and control) and TFV (a microbicide candidate which is proven to be efficacious and safe [1]) were chosen as negative controls. N9 and TFV were purchased from LKT Laboratories, Inc., and Molekula Limited (United Kingdom), respectively.…”
Section: Reagentsmentioning
confidence: 99%
“…Most interestingly, we also found that three adhesion molecules, L-selectin, P-selectin, and VCAM-1, exhibited significant increases after N9 treatment. In previous studies of soluble biomarkers for microbicidal safety, most attention was focused on proinflammatory cytokines and chemokines, while little attention was given to soluble adhesion molecules (2,9,13,15,16,39). Actually, it is well documented that adhesion molecules play a pivotal role in the onset and progress of inflammation and inflammatory diseases (5,23,25).…”
Section: Identification Of Novel Protein Molecules Related To Cervicomentioning
confidence: 99%
See 1 more Smart Citation